SAT0598-HPR Valued Life Activities: Swedish Version (VLA-SWE) with Cultural Adaptation, ICF Linkage and Psychometric Testing. (23rd January 2014) - Björk, M.; Thyberg, M.; Waltersson, E.; Stenström, B.; Katz, P.
Abstract : Background: Disability is an important outcome in rheumatoid arthritis (RA). The Valued Life Activity scale (VLA) comprises a wide range of life activities deemed to be important by the individual, ranging from self-care to leisure activities. Thereby VLA takes the patients´ priorities into account and includes activities in which disability may occur early. Objectives: Translation, cultural adaptation including linkage to the International Classification of Functioning, Disability and Health (ICF) and psychometric testing of the VLA scale in Swedish patients with RA. Methods: The VLA, developed by Katz et al (1 ) was translated and culturally adapted to a Swedish version, the VLA-swe. As a part of this, both the VLA and VLA-swe were linked to the ICF according to linking rules (2 ). 737 RA patients(73% women)aged 18 - 80 (mean age 62 years) were recruited from the Swedish Rheumatology Quality Registry (SRQ). The average disease duration was 16 years. Data for disease activity (DAS28), activity limitations (HAQ) and life satisfaction (LiSat11) were registered and patients completed the VLA-swe. Internal consistency was assessed with Cronbach's alpha and item statistics. To establish construct validity VLA-swe was correlated to DAS28, HAQ and LiSat11. Results: The conceptual similarity between the VLA-swe and the original VLA was high when linked to the ICF: in 29 of the 33 items the ICF codes tallied exactly with each other and the remaining differed only slightly. Each of the 9 ICF activity/participation domains was represented in one or more items. The internal consistency was excellent for the VLA-swe (0.97) and alpha coefficients did not improve after omitting any of the 33 items. The correlations between the single items and the total VLA-swe score varied between r=0.57 and r=0.84. Scores of the VLA-swe correlated strongly with the HAQ (r=0.87), moderately with the LiSat11 (r=-0.61) and weakly with the DAS28 (r=0.38), as expected. Conclusions: The VLA-swe is culturally adapted and validated, and addresses a broad range of ICF activity/participation domains. Since both the patients´ preferences and ICF concepts of disability are taken into account, it is a useful complement to traditional measures, such as the HAQ, which measure activity limitations only. References: Katz P, Morris A, Yelin E. Prevalence and predictors of disability in valued life activities among individuals with rheumatoid arthritis. Ann Rheum Dis 2006;65:763e9. Cieza A, Geyh S, Chatterji S, Kostanjsek N, Ustun B, Stucki G. ICF linking rules: an update based on lessons learned. J Rehabil Med 2005;37:212-218. Disclosure of Interest: None Declared